Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T17:54:49+01:00
A) (2x + 4y) - (5 + 2x) - (3y - 5) dla x = 1 i y = 2
(2+8 )- (5+2) -(6-5)= 10-7-1= 2

b) 4a² - (3a - 4a + 1)-(-2a² + a) dla a = - 3

36-(-9+12+1)-(-18-3)= 36+9-12-1+18+3=53
2010-03-06T18:01:14+01:00
A)
(2x + 4y) - (5 + 2x) - (3y - 5) =
2x+4y-5-2x-3y+5 =
2*1+4*2-5-2*1-3*2+5 =
2+8-5-2-6+5 =
2

b)
4a² - (3a - 4a + 1)-(-2a² + a) =
4a²-3a+4a-1+2a²-a =
4*(-3)²-3*(-3)+4*(-3)-1+2*(-3)²-(-3) =
4*9+9-12-1+2*9+3 =
36+9-12-1+18+3 =
53

2010-03-06T18:04:09+01:00

a) (2*1 + 4*2) - (5+2*1) - (3*2 - 5)=
=(2+8) - (5+2) - (6 - 5)=
=10-7-1=2

b) 4*-3 do potęgi2 -(3*-3 - 4*-3 +1)-[-2*-3 do p2 +(-3)]=
= 36 - ( -9 - 12 +1)-(-18 +(-3))=
= 36 +9 + 12 -1+ 18 +3=
= 77